(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Based on a previous test (fractionation) on Nephrolepis biserrata, lignocellulose contains 34.27% of pectin and oligosacharides, 1.78% of hemicellulose, 20.66% of cellulose and 43.29% of lignin. The optimum time for extraction of pectin from Nephrolepis biserrata leaves was investigated. Extraction time of 60, 90, 120 minutes at pH 1.5 and temperature of 80Â°C were found to significantly affect the extraction of pectin from Nephrolepis biserrata leaves. Maximum pectin yield is 15.8%, which was obtained in sulphuric acid solution of pH 1.5 at 80Â°C for 120 minutes.Â